The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.1071/cp22299
|View full text |Cite
|
Sign up to set email alerts
|

Reducing enteric methane of ruminants in Australian grazing systems – a review of the role for temperate legumes and herbs

Abstract: For full list of author affiliations and declarations see end of paper In Australia, 71% of agricultural greenhouse gas (GHG) emissions are enteric methane (CH 4 ), mostly produced by grazing sheep and cattle. Temperate low CH 4 yielding legumes and herbs can mitigate

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 145 publications
(336 reference statements)
0
7
0
Order By: Relevance
“…According to TOPSIS, the best alternative is the one geometrically closest to the positive ideal solution and the farthest away from the negative ideal solution. As a technique to implement MCDM, TOPSIS has become a sound mathematical tool capable of guiding ideal solutions to challenging situations [16]. The application of MCDM through TOPSIS has resulted in a more efficient use of resources, improved decisions, and better risk management [22][23][24].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to TOPSIS, the best alternative is the one geometrically closest to the positive ideal solution and the farthest away from the negative ideal solution. As a technique to implement MCDM, TOPSIS has become a sound mathematical tool capable of guiding ideal solutions to challenging situations [16]. The application of MCDM through TOPSIS has resulted in a more efficient use of resources, improved decisions, and better risk management [22][23][24].…”
Section: Methodsmentioning
confidence: 99%
“…Several articles, namely Badgery et al [16], Stifkens et al [50], and Mwangi et al [13], investigated a number of legumes and herbs for impact on CH 4 reduction in ruminant diets. Badgery et al [16] found that Biserrula pelecinus has great potential to reduce enteric CH 4 emissions, similarly to clover Trifolium subterraneum.…”
Section: Feed Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Oram (1993) outlined the reasons for expanding the number and area of alternative legumes as: (1) the need to fill diverse ecological niches within paddocks; (2) better buffering against pests and diseases; and (3) improving sustainable soil management. In addition, recent research has shown that alternative legumes may have a role in reducing methane emissions from livestock (Badgery et al 2023) and reducing incidence of metabolic disorders in livestock associated with issues such as bloat (Marshall et al 1979) and mineral imbalance (Refshauge et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Badgery et al . (2023) reviewed the role that pasture legumes and herbs can have in reducing enteric methane emissions from ruminant animals, highlighting an important future research area in pasture-based livestock production.…”
mentioning
confidence: 99%